Burden of rare variants in arrhythmogenic cardiomyopathy with right dominant form‐associated genes provides new insights for molecular diagnosis and clinical management. Issue 9 (23rd July 2022) - Goudal, Adeline; Karakachoff, Matilde; Lindenbaum, Pierre; Baron, Estelle; Bonnaud, Stéphanie; Kyndt, Florence; Arnaud, Marine; Minois, Damien; Bourcereau, Emmanuelle; Thollet, Aurélie; Deleuze, Jean‐François; Genin, Emmanuelle; et al.
Abstract: Arrhythmogenic cardiomyopathy with right dominant form (ACR) is a rare heritable cardiac cardiomyopathy disorder associated with sudden cardiac death. Pathogenic variants (PVs) in desmosomal genes have been causally related to ACR in 40% of cases. Other genes encoding nondesmosomal proteins have been described in ACR, but their contribution in this pathology is still debated. A panel of 71 genes associated with inherited cardiopathies was screened in an ACR population of 172 probands and 856 individuals from the general population. PVs and uncertain significance variants (VUS) have been identified in 36% and 18.6% of patients, respectively. Among the cardiopathy‐associated genes, burden tests show a significant enrichment in PV and VUS only for desmosomal genes PKP2 (plakophilin‐2), DSP (desmoplakin), DSC2 (desmocollin‐2), and DSG2 (desmoglein‐2). Importantly, VUS may account for 15% of ACR cases and should then be considered for molecular diagnosis. Among the other genes, no evidence of enrichment was detected, suggesting an extreme caution in the interpretation of these genetic variations without associated functional or segregation data. Genotype–phenotype correlation points to (1) a more severe and earlier onset of the disease in PV and VUS carriers, underlying the importance to carry out presymptomatic diagnosis in relatives and (2) to a more prevalent left ventricular dysfunction in DSP variant carriers.